Enhancing MSME Awareness on Halal Certification: A Community-Based Socialization Approach - Nurul Hidayah; Anggun Sugesti; Cinta Davia Putri Avrilusita; Firli Putri Gunawan; Ira Orlensyah; Jaka Nugraha (Smart Society, 2023)
Halal product certification plays a crucial role in ensuring product safety, enhancing consumer trust, and expanding market opportunities, particularly for Micro, Small, and Medium Enterprises (MSMEs). However, many MSME owners lack awareness of its importance and face challenges in the certification process due to limited knowledge and resources. This community service program, conducted in Bujung Buring Village, Tanjung Raya District, Mesuji Regency, Lampung Province, aims to address these issues by increasing MSMEs' understanding of halal certification and assisting them in obtaining certification. The study employs the Participatory Action Research (PAR) method, integrating research with social change by involving MSMEs throughout the planning, implementation, and evaluation stages. The program includes potential and problem mapping, certification awareness campaigns, and direct assistance in the halal certification registration process. The results indicate a significant improvement in MSME owners’ understanding of halal certification. Additionally, MSMEs reported increased confidence in marketing their products to a broader consumer base. This initiative demonstrates the effectiveness of community-based interventions in promoting halal certification and can serve as a model for similar programs in other regions. Further research and policy support are recommended to sustain and expand halal certification initiatives for MSMEs, ensuring wider adoption and compliance with halal product regulations.